6+2x=4x-2

Simple and best practice solution for 6+2x=4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x=4x-2 equation:


Simplifying
6 + 2x = 4x + -2

Reorder the terms:
6 + 2x = -2 + 4x

Solving
6 + 2x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 2x + -4x = -2 + 4x + -4x

Combine like terms: 2x + -4x = -2x
6 + -2x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -2x = -2 + 0
6 + -2x = -2

Add '-6' to each side of the equation.
6 + -6 + -2x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = -2 + -6
-2x = -2 + -6

Combine like terms: -2 + -6 = -8
-2x = -8

Divide each side by '-2'.
x = 4

Simplifying
x = 4

See similar equations:

| 2x+1=10x-3(x-1) | | 3y^2-15y=12 | | x^2+x-80=0 | | 6y+7=5y-5 | | 4a+2b-3-6a-5b= | | 5.5y=71.5 | | 7-6a=7a | | -3(4y-2)-y=-3(y-5) | | -2x^2+6x+8=0 | | 3x+2(x+3)=31 | | 14x-(4+5x)= | | (-11)-18= | | 2x+5(x-4)=36 | | 4(xy)=(4y) | | 6+10(15)= | | 4x+11=-12x-37 | | 6n^2-21n-15=0 | | (W-5)(2w+7)= | | 3x+3(x-2)=30 | | 10x+8=3(3x+1) | | 9x+7(-x-10)+14-3x= | | 4(xy)=(4x) | | 16x-(8+7x)= | | -11+18= | | -0.7(-7.54+5x)=-2.7x | | 6x-7-2x+4=4(-3x-5)-17 | | 13=16+3d | | 0=-16t^2+290 | | 636-x=85 | | u(v+6)+w(v-9)=z(v-1) | | 5y+3x-3=0 | | 8-3(x-2)=2x |

Equations solver categories